EFFECTIVENESS OF TREATMENT AND PREVENTION OF FELINE CALICIVIRUS (FC) IN VETERINARY CLINIC LLC «BIOCENTER» IN POLTAVA - Коне, М. С.; Корчан, Л. М.; Держговська, Є. О.; Забіяка, О. О. (Scientific Progress & Innovations, 2015)
The age and breed sensitivity, seasonal occurrence and dynamics of FC manifestation in veterinary clinic of LLC «Biocenter» in Poltava was studied. A variety of treatment regimens of FC was offered. We etablished that FC is often recorded among cats aged from two months till one year. More prone to the disease are outbred animals. The disease has an expressed seasonality, which appeared by frequent events in spring-summer-autumn period. Our offered treatment of FC provides high therapeutic effectiveness.